Targeting of Topoisomerase I for Prognoses and Therapeutics of Camptothecin-Resistant Ovarian Cancer - Lee, Yu-Chieh (PLoS One, 2015)
DNA topoisomerase I (TOP1) levels of several human neoplasms are higher than those of normal tissues. TOP1 inhibitors are widely used in treating conventional therapy-resistant ovarian cancers. However, patients may develop resistance to TOP1 inhibitors, hampering chemotherapy success. In this study, we examined the mechanisms associated with the development of camptothecin (CPT) resistance in ovarian cancers and identified evodiamine (EVO), a natural product with TOP1 inhibiting activity that overcomes the resistance. The correlations among TOP1 levels, cancer staging, and overall survival (OS) were analyzed. The effect of EVO on CPT-resistant ovarian cancer was evaluated in vitro and in vivo. TOP1 was associated with poor prognosis in ovarian cancers (p = 0.024). EVO induced apoptosis that was detected using flow cytometry and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay. The tumor size decreased significantly in the EVO treatment group compared with the control group (p < 0.01) in a xenograft mouse model. Effects of drugs targeting TOP1 for prognosis and therapy in CPT-resistant ovarian cancer are anticipated. EVO with TOP1 can be developed as an antiproliferative agent for overcoming CPT resistance in ovarian cancers.